Astrovirus Research Essential Ideas, Everyday Impacts, Future Directions - Schultz-Cherry, Stacey.; Schultz-Cherry, Stacey. (Springer New York : Imprint: Springer, 2013)
Since their initial discovery in the 1970’s, astroviruses have been recognized as a leading cause of enteritis in infants, the elderly, and immunocompromised people, and were known to be widespread in animals and birds. In recent years, and with the advent of  pyrosequencing, there has been a virtual explosion in the number of newly identified astrovirus genotypes. With this has come an increased understanding in astrovirus biology, structure, epidemiology, immunology, and disease pathogenesis including the likelihood of extraintestinal and systemic infections. The advent of new diagnostic tests that detect all of the currently identify human astrovirus strains may prove that these viruses are more prevalent in populations than currently realized. This book will provide state-of-the-art information on our current understanding of astroviruses for researchers, medical and veterinary providers, and diagnosticians as prepared by the leaders in the respective fields. The goal is to bring the reader up to date on the state of knowledge on this constantly evolving and exciting field of virology.